Creativity of Islamic Religious Education Teachers in the Student Characters Building - Siti Rusmiyatun; Muhammad Yusuf; Tukiran Tukiran (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2020)
Creative teacher is a teacher who has creativity or as an innovator. So that creativity does not appear suddenly but rather the amount of experience gained by the teacher in the learning process by preparing learning methods, preparing the tools used, and the material that will be delivered in the learning process. This study aims to reveal the creativity of Islamic Religious Education teachers in Character Building of State Middle School 4 Blambangan Umpu students. This study used a qualitative approach with case study design. Data collection is done by interview, observation and documentation. The results showed that: (1) able to convey material with creative models and methods and provide role models for students both in learning and outside of learning, (2) need to process to cultivate character and in still student awareness, (3) there is encouragement and motivation (press) from within namely the principal and teachers, while encouragement from the outside are parents, okoh adat and local government. (4) The realization of habitual characterization that is often applied in schools or in the community. (5) The supporting factors for character development in schools are from school principals, teachers, PGAI organizations and local governments, while the inhibiting factors are the less cultured community environment.